DAMPAK PARIWISATA TERHADAP PERKEMBANGAN DESAIN PERAK - Suharto Suharto (LPPM UNY, 2004)
Abstract The objective of this study is to know how the impact of tourism visits in Yogyakarta toward the development of the silver industry art in Yogyakarta is. The finding of the study shows that the impact of tourism in Daerah Istimewa Yogyakarta toward the development of the art of the silver industry in Kotagede can be classified in three period according to the government slogan. They are; the first period of Visit Indonesia year that was designed in the year 1986. It had impact in 1987 to 1990; the number of tourists increased from the yearly rate of 592,393 tourist. In the second period, the Visit Indonesia Year 1991 the number of tourists yearly reached 762,758 tourists. In the third period of Visit Asean Year 1992 to Go Indonesia 1998, the yearly rate of the number of the tourists achieved 935,537 tourists. Basically, the form result of silver industry art can be categorized into three kinds of forms, they are: the forms of accessories, furnishings, and decorations. The impact the first period to the development of the silver industry art design in Kotagede refers to the form of decoration that is dominated by the forms of miniature which are relatively big, complex, and there are still many forms dominated by linear lines especially in the form of accessories. In the second period, the number of form was developed more with many variations, form the size dimension; however it was smaller and lighter in weight. The form began to be out of the linear lines. In the third period, the design development used more material, application such as silver and gold, silver and copper, silver and tortoise shell, silver and wood, etc. Keywords:silver design